THE FINANCIAL SERVICES AUTHORITY (OJK) IN SUPERVISING THE BANK PAYMENT SYSTEM AND PROTECTING CUSTOMERS AGAINST CRIMINAL ACTS - Matwar, Habib; Rokan, Mustapa Khamal (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The role of the OJK in regulating and supervising Fintech is to minimize risks so as to provide good and stable growth. The research method used is qualitative research using a case study approach model through interviews, document observation or reports by describing the object of the research case. Data sources come from primary data in the form of interviews and secondary data in the form of books and websites. The subject of this research is the protection and education section of the Financial Services Authority. The results of the research show that there are indeed violations occurring in the financial services sector which are handled by the Financial Services Authority. OJK has also carried out one of its roles, namely education, by holding several workshops or seminars held at several institutions as well as in regions for the general public.